A research history of Laestadianism in Norway: From the 1960s to the present day - Larsen, Rolf Inge (Approaching Religion, 2020)
This article provides an overview and discusses the history of research on Laestadianism in Norway over the last 60 years. Research history earlier than 1960 and doctoral theses are discussed in this issue of Approaching Religion by Roald E. Kristiansen and Bengt-Ove Andreassen. It gives an impression of the nuances in approach between different academic disciplines and also different insider perspectives on Norwegian Laestadianism. The article shows that there is a need for comparative research on Laestadianism in Norway between different geographic regions and academic disciplines.